2017
DOI: 10.17305/bjbms.2017.2457
|View full text |Cite
|
Sign up to set email alerts
|

Matrine induced G0/G1 arrest and apoptosis in human acute T-cell lymphoblastic leukemia (T-ALL) cells

Abstract: Matrine, a natural product extracted from the root of Sophora flavescens, is a promising alternative drug in different types of cancer. Here, we aimed to investigate the therapeutic effects and underlying molecular mechanisms of matrine on human acute lymphoblastic leukemia (ALL) cell line, CCRF-CEM. Cell viability and IC50 values were determined by WST-1 cell cytotoxicity assay. Cell cycle distribution and apoptosis rates were analyzed by flow cytometry. Expression patterns of 44 selected miRNAs and 44 RNAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Interestingly, mmu-miR-106b-3p was the only one target miRNA that was up-regulated in NASH mice and downregulated in YBT treated mice. Abnormal expression of miR-106b-3p has been found in several types of cancers (Lu et al, 2014;Wang et al, 2017), which is associated with cell cycle (Vardarli et al, 2018), cell proliferation and mesenchymal transition (Qiao et al, 2019). Recently, it was found that, miR-106b-3p was down-regulated when human retinal pigment epithelium cell was incubated with H 2 O 2 (Ayaz and Dinc, 2018), while circulating miR-106b-3p exhibits an increased level in HCC patients compared with cirrhosis patient or healthy control (Moshiri et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mmu-miR-106b-3p was the only one target miRNA that was up-regulated in NASH mice and downregulated in YBT treated mice. Abnormal expression of miR-106b-3p has been found in several types of cancers (Lu et al, 2014;Wang et al, 2017), which is associated with cell cycle (Vardarli et al, 2018), cell proliferation and mesenchymal transition (Qiao et al, 2019). Recently, it was found that, miR-106b-3p was down-regulated when human retinal pigment epithelium cell was incubated with H 2 O 2 (Ayaz and Dinc, 2018), while circulating miR-106b-3p exhibits an increased level in HCC patients compared with cirrhosis patient or healthy control (Moshiri et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, downregulation of miR-21, followed by the dephosphorylation of its target Akt, was reported also by the growth-inhibiting alkaloid matrine, on breast cancer cells [181]. Similar involvement of miR-21 by alkaloids was observed on human thyroid cancer cells [182], while other miRs were involved in other cells, i.e., miR-19b in melanoma [183], miR-106b in human acute T-cell lymphoblastic leukemia [184], and miR-126 in non-small-cell lung cancer [185].…”
Section: Plant-based Alkaloidsmentioning
confidence: 78%
“…The tumor volume and tumor weight were declined by MAT and were elevated due to LINC00472 knockdown. As a type of extract of Chinese traditional medicine radix sophorae flavescentis, researches had pointed out that MAT could induce cell apoptosis 26 and played a protective role in carcinoma. For instance, a research pointed out that MAT restrained cell proliferation in pancreatic carcinoma 27 while the other research pointed out that MAT restrained cell migration in lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%